Peningkatan Pengetahuan Masyarakat Desa Jelantik Dalam Menghadapi Pandemi Corona Virus Diseases–19 (Covid-19) - Sulaeman Sulaeman; Supriadi Supriadi (Jurnal Pengabdian UNDIKMA, 2020)
The emergence of Corona Virus Diseases-19 outbreaks encourages the importance of educating and raising awareness about the importance of a clean and healthy lifestyle. In addition, the community needs to know with certainty the transmission and prevention of Covid-19 so that it does not become an epidemic in Jelantik Village, Central Lombok Regency. The purpose of this community service activity is to provide a scientific picture and be easily understood by the community at the level of the Hamlet and Jonggat Village to anticipate the outbreak of the Covid-19 pandemic. The activity stage was designed for 2 days, which was preceded by coordination and communication with the Jonggat village. Preparation intended is the determination of the direction and target of activities, activity models, follow-up activities and locations of activity concentration. The results of this activity are very much in line with what was expected, namely the activities carried out by the people who were present actively asking about the material provided. This shows that their great curiosity and high attention of participants to increase their knowledge about how to prevent and deal with Covid-19 and how to maintain good personal and environmental health